Serial and Parallel Processes in Working Memory After Practice. - Oberauer, Klaus; Bialkova, Svetlana (Journal of Experimental Psychology. Human Perception & Performance, 2011)
Six young adults practiced for 36 sessions on a working-memory updating task in which 2 digits and 2 spatial positions were continuously updated. Participants either did 1 updating operation at a time, or attempted 1 numerical and 1 spatial operation at the same time. In contrast to previous research using the same paradigm with a single digit and a single dot, dual-task costs were not eliminated with practice. Costs of switching between digits and between spatial positions were found throughout practice, supporting the existence of a focus of attention in working memory that can hold 1 digit and 1 spatial position simultaneously, but is not expanded to hold 2 elements of the same kind. The results can be understood by assuming that observed limits on parallel processing, as well as on the capacity of the focus of attention, arise not from structural constraints but rather reflect the optimal configuration of the cognitive system for avoiding information cross-talk in a given task. Reprinted by permission of the publisher.